Exploring Ethnomathematical Geometry in Indonesian Shadow Puppetry Gunungan: Philosophical and Educational Implications - Miftakhul Djannah; Naufal Ishartono; Argenti Agung Hayuni; Atikah Mufidah; Suliadi Fidaus bin Sufahani; Mohamad Waluyo (Jurnal VARIDIKA, 2024)
This study delves into the philosophical dimensions of traditional architecture and the ethnomathematical geometry inherent in the mountains of shadow puppets, a significant aspect of Indonesia's cultural heritage. Utilizing a qualitative methodology with an ethnographic design, data were collected through observations and interviews with primary, secondary, and additional informants. The objective of this research is to uncover the mathematical concepts embedded in the mountains of shadow puppets, including geometry, algebra, arithmetic, and statistics, using an ethnographic approach that addresses four principal inquiries: "Where should I begin my investigation?", "How do I proceed with the search?", "How can I identify significant findings?", and "How do I interpret these findings?". The results indicate that among the four mathematical concepts investigated, only geometric concepts are present in the puppet mountains, as validated by a geometer. The geometric sub-concepts identified encompass (1) geometric transformations such as translation and reflection, (2) plane geometry including rhombuses, rectangles, triangles, and circles, and (3) congruence and symmetry. This research holds significant implications for enhancing students' mathematical education by incorporating geometric examples from local cultural contexts. Integrating ethnomathematics into school curricula can expand students' artistic horizons, boost their engagement in learning, and deepen their comprehension of mathematical concepts.